Removal of Cu(II) from aqueous solutions by using marble waste - Arslanoglu, Hasan (Pamukkale Univ, 2017)
In this study, the effects of temperature, Cu(II) concentration, adsorbent dose, size and mixing speed were investigated on depending contact time in removal of Cu(II) ions from aqueous solutions with a adsorbent marble waste. When marble waste was used as an adsorbent removal efficiency of Cu(II) was determined to be 89.2% at 200 rpm stirring speed; optimum dosage of adsorbent was 10 g/L and sorption efficiency at this dose was determined to be 83.4%. The kinetic data fit the pseudo second order kinetic model. Activation energy for Cu(II) sorption process were found to be 9.35 kJ/moL The adsorption equilibrium data for the Cu(II) sorption process obeyed well for Langmuir isotherm and the maximum sorption capacity were calculated to be 208.33 mg/g for 25 degrees C. Thermodynamic parameters indicated this the Cu(II) adsorption process were endothermic (Delta G degrees=12.88 kJ/mol) and spontaneous (Delta H degrees=-8.56 kJ/mol).
Keywords: Copper; Adsorption; Precipitation; Marble waste